2022
DOI: 10.3390/life12030456
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Human Microbiome for Health

Abstract: Microorganisms are an essential part of life on the earth and can exist in association with virtually any living thing. The environmental microbiome is much more diverse than the human microbiome. It is reported that most microbes existing in the environment are difficult to culture in the laboratory. Whereas both pathogenic and beneficial microbes may be prevailing in the environment, the human body can have three categories of microbes- beneficial, pathogenic, and opportunistic pathogenic. With at least 10-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Specifically, indoor microbiota can be shaped according to the diversity and composition of soil and plants by transferring outdoor microbes indoors and adding houseplants to built-in interiors (Roviello et al, 2021). To an increasing extent, studies have shown that the interaction between human and environmental microbiomes affects human health and the prevalence of NCDs (Ahn and Hayes, 2021;Panthee et al, 2022). Roslund et al (2022) investigated the impact of biodiversity on immune tolerance using a double-blind and placebo-controlled intervention trial.…”
Section: Figurementioning
confidence: 99%
“…Specifically, indoor microbiota can be shaped according to the diversity and composition of soil and plants by transferring outdoor microbes indoors and adding houseplants to built-in interiors (Roviello et al, 2021). To an increasing extent, studies have shown that the interaction between human and environmental microbiomes affects human health and the prevalence of NCDs (Ahn and Hayes, 2021;Panthee et al, 2022). Roslund et al (2022) investigated the impact of biodiversity on immune tolerance using a double-blind and placebo-controlled intervention trial.…”
Section: Figurementioning
confidence: 99%
“…There are abundant microorganisms (known as the microbiota) that live inside the human body and on the skin surface, which far outnumbers the body's somatic cells (Turnbaugh et al, 2007). Human microbes can be divided into three categories-beneficial, pathogenic and opportunistic and they play a vital role in maintaining human health (Panthee et al, 2022). The change of microbial diversity in the human body is related to diseases in various parts of the human body, including the skin, gastrointestinal tract, urinary tract, reproductive tract, and other disease-prone parts (Binek, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These associations could reflect the direct impacts of environmental microbial exposure on inhabitants' health, as well as through indirect effects of dust microbiota on the human gut, skin, oral, and respiratory microbiomes (6)(7)(8). Housing characteristics and other environmental exposures have been shown to influence indoor microbial communities, including farm-related exposures (8)(9)(10)(11). Living in or near a farm environment entails unique microbial exposures and subsequent health concerns.…”
Section: Introductionmentioning
confidence: 99%